2017
DOI: 10.31018/jans.v9i2.1263
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different growing media on the rooting of pomegranate (Punica granatum L.) cv. 'Phulearakta' cuttings

Abstract: To identify the most efficient growing medium for root and shoot development in stem cuttings of pomegranate cv. ‘Phulearakta’ under arid conditions, a greenhouse experiment was conducted in randomized complete block design with three replications during 2014-15 at ICAR-CIAH, Bikaner. About 15-20 cm long hard wood cuttings, 0.5-1.0 cm diameter and having three to four buds were separated from the healthy trees and planted in mid-January. Detached cuttings were treated with 2500 ppm of IBA (3- Indole butyric ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 9 publications
(10 reference statements)
8
16
0
Order By: Relevance
“…These results are in accordance with those obtained by Rajkumar et al (2016), Manila et al (2017) and Peña- Baracaldo et al (2018), who observed that vermiculite substrate was the best rooting medium in increasing the rooting percentage of many species cuttings than the other substrates. The main reasons in increasing the rooting percentage of C. erectus cuttings under vermiculite medium may be due to better aeration, excellent drainage, more water holding capacity and release of nutrients gradually from vermiculite medium resulting in better rooting percentages (Ansari, 2013;Manila et al, 2017).…”
Section: Rooting Percentagesupporting
confidence: 93%
See 4 more Smart Citations
“…These results are in accordance with those obtained by Rajkumar et al (2016), Manila et al (2017) and Peña- Baracaldo et al (2018), who observed that vermiculite substrate was the best rooting medium in increasing the rooting percentage of many species cuttings than the other substrates. The main reasons in increasing the rooting percentage of C. erectus cuttings under vermiculite medium may be due to better aeration, excellent drainage, more water holding capacity and release of nutrients gradually from vermiculite medium resulting in better rooting percentages (Ansari, 2013;Manila et al, 2017).…”
Section: Rooting Percentagesupporting
confidence: 93%
“…cuttings. The increment in rooting percentage of C. erectus stem cuttings treated with different concentrations of IBA, especially at 100 ppm could be due to the effect of auxins in enhancing the root ability of stem cuttings through their ability to promote the initiation of root primordia and to enhance the translocation of carbohydrates, rooting co-factors and nitrogenous substances from leaves to the base of cuttings for enhancing adventitious root formation (Rajkumar et al, 2016). Besides, auxins help in elongation of meristematic cells and differentiation of cambial initial into root primordial (Nanda, 1975).…”
Section: Rooting Percentagementioning
confidence: 99%
See 3 more Smart Citations